(untitled) (Atti del Sodalizio Glottologico Milanese, 2017)
This article discusses some practical problems of translation and translating on the basis of various Western and Eastern languages and literatures. Many issues and facets will be considered: the case of philosophical or speculative texts; technical literature; poetry and its puzzles; puns; and various others. KEYWORDS: Translation; philosophical and technical literature; poetry; Taoism; Buddhism